Meningkatkan Keterampilan Guru Membuat Aplikasi Pembelajaran Interaktif Berbasis Android - Dwijoko Purbohadi; Titis Wisnu Wijaya; Devina Shifra Ramadhani; Nisrina Akbar Rizky Putri; Novi Diah Wulandari (I-Com: Indonesian Community Journal, 2024)
Learning technology greatly enriches teachers' experiences by enhancing their teaching skills. Teachers can optimize online tools and resources, facilitate more flexible/collaborative teaching, and conduct learning assessments easily and quickly. Despite providing significant benefits, this technology demands quick adaptability from teachers to keep up with changes and new educational challenges. Many schools require training activities or learning technology upgrades, including Muhammadiyah schools in Wates Yogyakarta. This service program aims to provide training for teachers on how to optimize the use of interactive e-learning. The service program is an initiative in collaboration with SMP Muhammadiyah 2 Wates as a partner. Its goal is to enhance the skills of teachers at partner locations in utilizing learning technology. The service activities start with planning stages through needs identification, goal setting, platform selection, and curriculum review. Subsequently, program implementation includes teacher training, assignments, and further mentoring. The primary training program materials include multimedia theory, PowerPoint, and iSpring.